Detection of Oral Human Papillomavirus (HPV) and its Clinical Importance - Gabriela Nalli; Paula Mastrotta; María Gabriela Garcia; Silvio Tatti; Sergio Verdú (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Human papillomavirus (HPV) has a tropism for the squamous epithelium and cause a wide range of diseases, from benign lesions to invasive tumors that can affect the oral cavity. Purpose: This study aimed to estimate HPV infection in compatible stomatological lesions. Materials and Method: A cross-sectional study was carried out from March 2017 to August 2019, which included patients who attended the Oral Medicine Department of the School of Dentistry of the University of Buenos Aires who presented oral manifestations compatible with HPV infection that accepted to be studied by histopathology and determination of viral genotype by polymerase chain reaction (PCR). The study was carried out from the biopsy fixed in formalin and included in paraffin, for histopathological study and the genotypification of HPV by genotype-specific PCR and/or sequencing of the L1 fragment. To confirm the negative cases hybrid capture method was also used. The 95% OR-IC was estimated. Results: 108 patients, 76 women and 32 men were studied, who underwent a clinical stomatological examination and genotyping of HPV (PCR-specific genotype), being positive for 60 patients and negative for 48. Among the positive cases (n= 60) 46.7% (n= 28) corresponded to elevated lesions infected with high-risk HPV genotypes, 43.3% (n= 26) to elevated lesions with low-risk HPV genotypes, regarding flat lesions it was found that 5% (n=3) corresponded with high-risk HPV genotypes and another 5% (n=3) with low-risk genotypes, with OR 1,076 95% CI (0.1993-5.818). The HPV genotypes found were 2, 6, 11, 13, 16, 18, 26, 31, 32, 33, 35, 51, 58, 64 and 72. Conclusion: Our results estimated an association between white, bright, and elevated oral lesions and the presence of high-risk HPV.